Pengembangan Sistem Ground Control Station Berbasis Internet Webserver pada Pesawat Tanpa Awak - Fredy Aga Nugroho; Raden Sumiharto; Roghib Muhammad Hujja (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
In unmanned aerial operations, the ground control station duties as a monitoring and command station so that operators on land can send mission orders, monitor the mission's course and monitor the condition of the UAV during the mission. It is necessary to have a GCS system capable of connecting with UAV that not limited with control transmitter range.This research develops GCS system using internet network and web server based. the system consists of two units, namely flying units and GCS units. The flying unit consists of Raspberry pi, modem, webcam, ADAHRS module and quadrotor with MultiWii controller. on the GCS unit consists of Raspberry pi connected on the internet network with 10Mbps download speed and 1.5Mbps upload.The GCS system can display aircraft conditions, stream video and perform command controls. Configure streaming video for delay time of no more than one second with 240x144 pixel resolution, 256kbps maximum bitrate and 5 fps framerate. This configuration runs at a 1.1 Mbps upload speed with a percentage of 93.83% bitrate compression. Aircraft condition data sent to GCS is optimal if internet bandwidth exceeds the bitrate of streaming video used on the system